Changes in echocardiographic indices and left ventricular strain values by two-dimensional speckle-tracking echocardiography following pre-anesthetic oral pimobendan administration compared with intravenous pimobendan in dogs - Jeong, Yijin; Kim, Bumseok; Kim, Sung-Soo; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2024)
The effects of pre-anesthetic single-dose oral pimobendan during inhalational anesthesia, including the comparison with the effects of single intravenous pimobendan under anesthesia, remain unexplored. Therefore, this study aimed to determine changes in hemodynamic and echocardiographic parameters induced by pre-anesthetic administration of oral pimobendan under isoflurane general anesthesia and to compare them with those induced by intravenous pimobendan. Methods: Thirteen clinically normal dogs (4 laboratory and 9 client-owned dogs) with no clinical signs and not on any medical treatment were included. Anesthesia was performed three times: no pimobendan (Control), oral pimobendan (PIMO PO, 0.3 mg/kg), and intravenous pimobendan (PIMO IV, 0.15 mg/kg). Echocardiographic and hemodynamic parameters were monitored at 30-minute intervals in all groups. Results: Compared to the Control group, end-systolic volume index (ESVI) and normalized left ventricular internal diameter at end-systole (LVIDSN) were significantly lower, and fractional shortening (FS) and ejection fraction (EF) were significantly higher in the PIMO PO and IV groups (P < 0.001). Global radial strain (GRS) was significantly higher in the PIMO PO and IV groups (P = 0.015).Conclusions: Under general anesthesia, oral pimobendan preserved LV systolic and myocardial function in a manner comparable to intravenous pimobendan. Pre-anesthetic administration of oral pimobendan can be used to compensate for cardiac systolic function in dogs who require therapeutic and diagnostic procedures under general anesthesia with potential risk of circulatory failure.